Transarterial chemoembolization combined with Huaier granule for the treatment of primary hepatic carcinoma: Safety and efficacy. Issue 29 (July 2017) - Zhao, Guang Sheng; Liu, Ying; Zhang, Qing; Li, Chuang; Zhang, Yue Wei; Ren, Zhi Zhong; Zhou, Jun; Zhang, Ming
Abstract : Abstract: To evaluate the safety and efficacy of transarterial arterial chemoembolization (TACE) with gelatin sponge particles (GSPs-TACE) and Huaier granule to treat primary hepatic carcinoma (PHC). A series of 62 patients with PHC were included between June 2009 and December 2011, and randomly assigned to a control (n = 31) or an experimental group (n = 31). The control patients received TACE with 350 to 560 μm GSPs plus lobaplatin chemotherapy. Patients in the experimental group received TACE plus Huaier granule. Treatment safety and mid-to-long-term efficacy were evaluated. Follow-up ranged from 12 to 24 months with a mean of 28.7 months. The 6- and 12-month overall survivals were 100% and 93.5% in the experimental group and 90.3% and 80.6% in control group, respectively. The difference in overall survival at 12 months was significant (χ 2 = 5.213, P < .05), but the difference in median survival in the experimental group (20.6 months) and control group (17.1 months) patients was not significant (χ 2 = 0.745, P > .05). The number of TACE procedures in the experimental group (2.9 ± 8.7) and control group (4.1 ± 7.3) patients was significantly different (χ 2 = 7.262, P < .05). The 6-month (87.1% vs. 73.3%, χ 2 = 5.945) and 12-month (72.4% vs. 64.3%, χ 2 = 6.384) tumor objective response rates in the experimental and control groups were significantly different ( P < .05). There were no statistically significant differences in the occurrence of treatment-related adverse reactions in the 2 groups. Transarterial chemoembolization with GSPs and Huaier granule was safe and effective for treating PHC patients.